Blood pressure lowering and major cardiovascular events in people with and without chronic kidney disease: meta-analysis of randomised controlled trials. - Ninomiya, T; Perkovic, V; Turnbull, F; Neal, B; Barzi, F; Cass, A; Baigent, C; Chalmers, J; Li, N; Woodward, M; MacMahon, S (2013)
OBJECTIVE: To define the cardiovascular effects of lowering blood pressure in people with chronic kidney disease. DESIGN: Collaborative prospective meta-analysis of randomised trials. DATA SOURCES AND ELIGIBILITY: Participating randomised trials of drugs to lower blood pressure compared with placebo or each other or that compare different blood pressure targets, with at least 1000 patient years of follow-up per arm. MAIN OUTCOME MEASURES: Major cardiovascular events (stroke, myocardial infarction, heart failure, or cardiovascular death) in composite and individually and all cause death. PARTICIPANTS: 26 trials (152,290 participants), including 30,295 individuals with reduced estimated glomerular filtration rate (eGFR), which was defined as eGFR <60 mL/min/1.73 m(2). DATA EXTRACTION: Individual participant data were available for 23 trials, with summary data from another three. Meta-analysis according to baseline kidney function was performed. Pooled hazard ratios per 5 mm Hg lower blood pressure were estimated with a random effects model. RESULTS: Compared with placebo, blood pressure lowering regimens reduced the risk of major cardiovascular events by about a sixth per 5 mm Hg reduction in systolic blood pressure in individuals with (hazard ratio 0.83, 95% confidence interval 0.76 to 0.90) and without reduced eGFR (0.83, 0.79 to 0.88), with no evidence for any difference in effect (P=1.00 for homogeneity). The results were similar irrespective of whether blood pressure was reduced by regimens based on angiotensin converting enzyme inhibitors, calcium antagonists, or diuretics/β blockers. There was no evidence that the effects of different drug classes on major cardiovascular events varied between patients with different eGFR (all P>0.60 for homogeneity). CONCLUSIONS: Blood pressure lowering is an effective strategy for preventing cardiovascular events among people with moderately reduced eGFR. There is little evidence from these overviews to support the preferential choice of particular drug classes for the prevention of cardiovascular events in chronic kidney disease.